Leveraging animal feed supply chain capabilities through big data analytics: a qualitative study - Abushaikha, Ismail; Bwaliez, Omar M.; Yaseen, Marwa; Hamadneh, Samer; Darwish, Tamer K. (Emerald, 2025)
Purpose Although big data analytics (BDA) has gained widespread interest in supply chain management (SCM) literature in recent years, our understanding of how it contributes to improved animal feed supply chains (SCs) is still underexplored. This study provides a greater understanding of the role of BDA in improving animal feed SC capabilities. Design/methodology/approach A qualitative approach was used in this study. Data were collected through 32 semistructured interviews from several actors involved in the production and supply of animal feed concentrates. Findings This study provides rich in-description evidence of how BDA enhances performance in the animal feed supply chain through improved logistics capabilities, quality control and information visibility. Our findings also suggest that organizational culture contributes to leveraging BDA capabilities in the feed-processing SCs. Practical implications The research provides an in-depth qualitative investigation of implementing big data in the feed processing SCs. The study provides practical implications for SC managers in the agri-food sector. Originality/value The study contributes to the growing body of knowledge by providing field evidence of the relevance of BDA to animal feed SCs. Moreover, this study adds to the existing literature by providing an understanding of the role of the internal culture of the organization in leveraging BDA capabilities in the SC.
Keywords: Animal feed supply chain; Big data analytics; Sustainable supply chain; Qualitative research; Logistics capabilities; 3509 Transportation, Logistics and Supply Chains; 35 Commerce, Management, Tourism and Services; Data Science; 12 Responsible Consumption and Production; Business & Management; 3507 Strategy, management and organisational behaviour